2018
DOI: 10.7567/apex.11.035001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of picosecond and nanosecond lasers for the synthesis of TiN sub-micrometer spherical particles by pulsed laser melting in liquid

Abstract: In this study, TiN submicrometer spherical particles were fabricated via pulsed laser melting in liquid using picosecond and nanosecond lasers applied to colloidal nanoparticles. The sizes of the obtained submicrometer spherical particles decreased as the pulse width decreased from nanoseconds to picoseconds. Further, the laser fluence required for fabricating submicrometer spherical particles by irradiation with a picosecond laser was lower than that with a nanosecond laser. This result suggests that the heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Therefore, the obtained particle sizes in size‐fluence diagram by different laser fluence are often along the phase boundary curve of the melting start (the blue curve in Figure 4). This trend is commonly observed for the relationship between laser fluence and particle size of various materials obtained by PLML using a nanosecond laser and small raw nanoparticles [9] …”
Section: Resultssupporting
confidence: 57%
“…Therefore, the obtained particle sizes in size‐fluence diagram by different laser fluence are often along the phase boundary curve of the melting start (the blue curve in Figure 4). This trend is commonly observed for the relationship between laser fluence and particle size of various materials obtained by PLML using a nanosecond laser and small raw nanoparticles [9] …”
Section: Resultssupporting
confidence: 57%
“…If the pulse duration is much shorter (e.g., ps pulses), homogeneous heating is unlikely and evaporation at the particle surface leads to nanoparticle byproducts even below the fragmentation threshold. To our best knowledge, there are just a few studies reporting ps-LML [45,[49][50][51]. Sakaki et al reported on burst-mode laser irradiation for homogeneous heating depending on the number of pulses and the interval between them to generate submicron spheres [50].…”
Section: Nanoparticle Size Modificationmentioning
confidence: 99%
“…Heating behaviour of single particle can be discussed via thermal diffusion length during pulsed laser heating [ 39 ]. For 7 ns (pulse width) laser irradiation, thermal diffusion length can be calculated to be 1340 nm for Au fairly larger than the particle size.…”
Section: Introductionmentioning
confidence: 99%